Suture thickness and transvaginal cervical cerclage outcomes - Battarbee, Ashley N. (Am J Obstet Gynecol MFM, 2019)
BACKGROUND: Cervical cerclage placement has been shown to benefit women who have cervical insufficiency, however, the best type of suture to use for transvaginal cerclage placement is unknown. OBJECTIVE: To evaluate the association between transvaginal cerclage suture thickness and pregnancy outcomes. STUDY DESIGN: Retrospective cohort study of women with a singleton, non-anomalous gestation who underwent history-, ultrasound- or physical exam-indicated transvaginal cerclage at a single tertiary care center (2013–2016). The primary outcome was gestational age at delivery. Secondary outcomes included preterm birth less than 34 weeks, chorioamnionitis, neonatal intensive care unit admission and composite neonatal morbidity. Baseline characteristics and outcomes were compared by thickness of suture material: thick 5mm braided polyester fiber (Mersilene® tape) versus thin polyester braided thread (Ethibond®) or polypropylene non-braided monofilament (Prolene®) with selection of suture type at the discretion of the provider. The association between thick suture and gestational age at delivery was estimated using Cox proportional hazard regression. Multivariable logistic regression was used to estimate the association between thick suture and the secondary outcomes. Effect modification of cerclage indication was also assessed. RESULTS: A total of 203 women met inclusion criteria: 120 (59%) with thick suture and 83 (41%) with thin suture. Of these, 130 women had history-indicated, 35 had ultrasound-indicated, and 38 had exam-indicated cerclages. Compared to women who had thin suture, women with thick suture were more likely to have had a history- or ultrasound-indicated cerclage, rather than exam-indicated cerclage, and more likely to have had a Shirodkar or cervico-isthmic approach, rather than McDonald. Women with thick suture were also more likely to have received progesterone and had placement at earlier gestational age, but there were no differences in cervical exam at placement. After adjusting for confounding factors, thick suture was associated with longer pregnancy duration among women with ultrasound-indicated cerclage (aHR 0.61, 95%CI 0.41–0.91) and exam-indicated cerclage (aHR 0.30, 95%CI 0.15–0.58), but not with history-indicated cerclage (aHR 1.27, 95%CI 0.83–1.94). Thick suture was also associated with lower odds of preterm birth < 34 weeks, chorioamnionitis and neonatal intensive care unit admission, compared to thin suture. CONCLUSION: Thick, compared to thin suture, for transvaginal cervical cerclage was associated with longer duration of pregnancy among women with ultrasound- and exam-indicated cerclages and lower odds of chorioamnionitis and neonatal intensive care unit admission among all women regardless of cerclage indication.